2-Methoxyestradiol Alleviates Experimental Autoimmune Uveitis by Inhibiting Lymphocytes Proliferation and T Cell Differentiation. (8th May 2016) - Xu, Linxinyu; Yang, Tianshu; Su, Shaobo; Wang, Fang
Abstract : Purpose . To investigate the effect of 2-Methoxyestradiol (2ME2) on experimental autoimmune uveitis (EAU) and the mechanism. Method . C57BL/6 male mice were used to establish the EAU model. 2ME2 was abdominal administrated in D0–D13, D0–D6, and D7–D13 and control group was given vehicle from D0–D13. At D14, pathological severity was scored. Lymphocyte reaction was measured using MTT assay. T cell differentiation in draining lymph nodes and eye-infiltrating cells was tested by flow cytometry. Proinflammatory cytokines production from lymphocytes was determined by ELISA. Result . The disease scores from 2ME2 D0–D13, 2ME2 D0–D6, 2ME2 D7–D13, and vehicle groups were 0.20 ± 0.12, 1.42 ± 0.24, 2.25 ± 0.32, and 2.42 ± 0.24 . Cells from all 2ME2 treated groups responded weaker than control (p < 0.05 ). The inhibitory effect of 2ME2 on lymphocyte proliferation attenuated from 2ME2 D0–D13 to 2ME2 D0–D6 and to 2ME2 D7–D13 groups (p < 0.05 ). 2ME2 treated mice developed fewer Th1 and Th17 cells both in draining lymph nodes and in eyes than control (p < 0.05 ). Lymphocytes from 2ME2 group secreted less IFN- γ and IL-17A than those from control (p < 0.05 ). Conclusion . 2ME2 ameliorated EAU progression and presented a better effect at priming phase. The possible mechanism could be the inhibitory impact on IRBP specific lymphocyte proliferation and Th1 and Th17 cell differentiation.